The Compound Effect of Cupping Therapy: Searching Beyond the Meridians - Mohamed K.M. Khalil; Saud AlSanad (MEDrang Inc., 2018)
Cupping therapy (CT) is used in Asia, Europe, and the Middle East and is prevalent in Muslim communities where it is recommended by the Prophet of Islam. The majority of modern, medical practitioners interested in CT, view it as a medical technique and distance themselves from the mechanisms proposed by traditional medicine. However, modern medicine does not offer a valid explanation for the mechanisms involved in CT. There is growing evidence of CT's effectiveness, specifically in chronic pain management when compared to an inactive control, but not against sham treatment. CT accompanied by religion and prayer, as it is in Muslim communities, cannot be considered to be equivalent to any procedures in modern medicine. "Whole System Research" may be the most appropriate trial design to test the ancient practice of CT efficacy whilst pending development of a novel placebo for assessing the connectivity of body and mind interventions.